2007
DOI: 10.1177/0093854807300758
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Subtypes of Criminal Psychopaths

Abstract: Psychopathy is an important construct in offender classification. Although several studies have suggested that there are two distinct subtypes of psychopaths, these studies have considerable limitations, including reliance on self-report measures, a failure to adequately address heterogeneity within the construct of psychopathy, and predictor-criterion contamination. A recent taxonomic study identified four subgroups of offenders, including primary and secondary psychopaths. We used cluster analysis to replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
88
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 58 publications
6
88
4
Order By: Relevance
“…The gender difference found in our study-low anxiety in boys and high influence of suicidal behaviour in girls-could indicate that psychopathy in boys corresponds to the primary subtype whereas psychopathy in girls might match with the secondary. Recent cluster analyses of adults have reported that measures of anxiety contribute to differentiation between groups of so-called primary psychopaths and secondary psychopaths [36,61,64,68]. Skeem and colleagues found in their sample of 367 adult male prison inmates that secondary psychopaths manifested more borderline personality features, poorer interpersonal functioning (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The gender difference found in our study-low anxiety in boys and high influence of suicidal behaviour in girls-could indicate that psychopathy in boys corresponds to the primary subtype whereas psychopathy in girls might match with the secondary. Recent cluster analyses of adults have reported that measures of anxiety contribute to differentiation between groups of so-called primary psychopaths and secondary psychopaths [36,61,64,68]. Skeem and colleagues found in their sample of 367 adult male prison inmates that secondary psychopaths manifested more borderline personality features, poorer interpersonal functioning (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have provided evidence for two distinct psychopath subtypes, these studies have inadequately addressed potentially important ethnic differences. A recent taxonomic study found evidence for primary and secondary psychopath subgroups in a sample of European American offenders (Swogger & Kosson, 2007). The present study used cluster analysis to attempt to replicate those findings in a sample of African American offenders.…”
mentioning
confidence: 67%
“…We also expected secondary psychopaths to have more criminal versatility than nonpsychopathic groups. Because findings have been mixed, we advanced no hypotheses regarding psychopathy subtypes and nonviolent charges.Prior subtyping studies have also identified an offender subgroup lacking psychopathic features (Swogger & Kosson, 2007;Vassileva et al 2005;Wales, 1995). Thus, we predicted a third cluster, consisting of individuals with lower scores on most measures of psychopathology.…”
mentioning
confidence: 77%
See 2 more Smart Citations